Development of red genetically encoded biosensor for visualization of intracellular glucose dynamics. Issue 1 (20th January 2022) - Mita, Marie; Sugawara, Izumi; Harada, Kazuki; Ito, Motoki; Takizawa, Mai; Ishida, Kentaro; Ueda, Hiroshi; Kitaguchi, Tetsuya; Tsuboi, Takashi
Summary: Glucose is the main source of energy for organisms, and it is important to understand the spatiotemporal dynamics of intracellular glucose. Single fluorescent protein-based glucose indicators, named "Red Glifons" have been developed that apply to live-cell and dual-color imaging. These indicators exhibited more than 3-fold increase in fluorescence intensity in the presence of 10 mM glucose. The two Red Glifons developed have different half-maximal effective concentration (EC50 ) values for glucose (300 μM and 3, 000 μM) and are able to monitor a wide range of glucose dynamics. Red Glifon combined with green indicators allowing visualization of the interplay between glucose and ATP, lactate, or pyruvate. Glucose influx in the pharyngeal muscle of Caenorhabditis elegans, enteroendocrine cells, and human iPS cell-derived cardiac myocytes was observed using the Red Glifons. Thus these red glucose indicators serve as a multi-color imaging toolkit for investigating complex interactions in energy metabolism. Graphical abstract: Highlights: Red Glifons are recently developed red fluorescent protein-based glucose indicators A wide range of glucose dynamics is detected in various species and tissues Interplay between glucose and other signaling molecules is visualized Up- and downregulation of glucose uptake during energy metabolism is observed Abstract : Mita et al. developed glucose indicators, Red Glifons, and visualized a wide range of intracellular glucose dynamics with other signaling molecules under a fluorescence microscope with high spatiotemporal resolution. They function in human cervical carcinoma cells, murine enteroendocrine cells, and iPS cell-derived human cardiac myocytes, and even in individual nematodes.